Optimization Study Of Time And Mass Of Ketapang Fruit Shell Biosorbent in the Methylene Blue Batch Adsorption Process - Meriatna, Meriatna; Zulmiardi, Zulmiardi; Nurlaila, Rizka; Suryati, Suryati; Hasfita, Fikri; Faisal, Faisal (Malikussaleh University, Aceh, Indonesia, 2025)
Ketapang fruit shell (Terminalia catappa) has shown potential as a low-cost, eco-friendly biosorbent for removing synthetic dyes from aqueous solutions. This study aimed to determine the optimum conditions for contact time and adsorbent mass of ketapang fruit shell in the adsorption of methylene blue dye. The research involved several stages: preparation and chemical activation of the fruit shells, batch adsorption experiments, analysis of adsorption capacity and efficiency, and optimization using the Response Surface Methodology (RSM). Characterization of the adsorbent was conducted using UV-Visible spectroscopy, Fourier Transform Infrared (FTIR) spectrosco-py, and Scanning Electron Microscopy (SEM) to analyze functional groups and surface morphology. The RSM approach was employed to evaluate the interaction effects of contact time and adsorbent mass, as well as to predict the optimal conditions for maximum dye re-moval. The optimum adsorption conditions were achieved at a contact time of 39.15 minutes and adsorbent mass of 0.416 g, resulting in an adsorption capacity of 1.935 mg/g and 100% removal efficiency. The regression model obtained from RSM was: Y= 35.13437 + 334.35597A – 1.67299B + 0.088354AB – 402.98656A² + 0.018207B², with a coefficient of determination R² = 0.7857 (78.57%), indi-cating a good model fit. Furthermore, the adsorption behavior followed the Freundlich isotherm model, supported by an R² value of 0.787 (78.7%), suggesting multilayer adsorption on a heterogeneous surface. These findings confirm the effectiveness of ketapang fruit shell as a promising adsorbent for methylene blue removal in wastewater treatment applications.